2015
DOI: 10.1111/nep.12364
|View full text |Cite
|
Sign up to set email alerts
|

Initiating acute dialysis at earlier Acute Kidney Injury Network stage in critically ill patients without traditional indications does not improve outcome: A prospective cohort study

Abstract: Presence of traditional indications at ARRT initiation was associated with greater mortality. Initiating dialysis at earlier AKIN stage did not improve survival in patients without traditional indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
(71 reference statements)
0
20
0
2
Order By: Relevance
“…Therefore, blood purification technology could be used to remove inflammatory factors, eliminate cytokine storm, correct electrolyte imbalance, and maintain acid-base balance, to control patient's capacity load in an effective manner [65]. In this logic, the patient's symptoms could be improved and the blood oxygen saturation could be increased.…”
Section: Auxiliary Blood Purification Treatmentmentioning
confidence: 99%
“…Therefore, blood purification technology could be used to remove inflammatory factors, eliminate cytokine storm, correct electrolyte imbalance, and maintain acid-base balance, to control patient's capacity load in an effective manner [65]. In this logic, the patient's symptoms could be improved and the blood oxygen saturation could be increased.…”
Section: Auxiliary Blood Purification Treatmentmentioning
confidence: 99%
“…[28,29] Several studies showed high survival rates and kidney recovery among patients who received early RRT. [3032] Recently, a single-center trial, [25] comparing early RRT with delayed RRT in patients with AKI trial, reported that early initiation resulted in a 15.4% reduction in 90-day mortality compared with delayed RRT (39.3% vs 53.6%; P  = 0.03). For the early group, RRT was initiated within 8 hours of diagnosis of stage 2 AKI using the Kidney Disease: Improving Global Outcomes (KDIGO) classification, while delayed RRT was initiated within 12 hours of stage 3 AKI.…”
Section: Discussionmentioning
confidence: 99%
“…This was a secondary analysis of prospectively collected data from a cohort study in a single-center 1782-bed tertiary-care hospital in Singapore [13]. All critically ill patients admitted to medical and surgical ICU between 18 December 2010 and 3 April 2013, who received acute RRT for AKI, were included.…”
Section: Methodsmentioning
confidence: 99%